The Role of Social Workers in the Elimination of Poverty in Lithuania - Žiukas, Vytautas (Socialinė teorija, empirija, politika ir praktika, 2001)
The goal of the paper is to present the role of social workers in the elimination of poverty in Lithuania. The context and establishment of strategy to eliminate poverty is presented in the fist part. The development of social support system gets special attention. It is argued the importance of social work in the elimination of poverty. The principles securing achievement and maintenance of social solidarity through social workers’ co-operation with their professional organisations are sketched in the final part.
Keywords: Poverty; Strategy; Social support system; Social work; Lithuania